ANALISIS STABILITAS LERENG DENGAN PERKUATAN BRONJONG MENGGUNAKAN SOFTWARE SLOPE/W ANALYSIS 2018 (KM 15+700) - Fernanda Disi Vera Agistin; Reki Arbianto; Sumina; Paska Wijayanti; Siti Farah Wahida Binti Mohamed (Journal of Civil Engineering and Infrastructure Technology, 2026)
The Grompol River is one of the rivers that crosses the Sragen area. The area around the lower reaches of the Grompol River in Sragen is vulnerable to slope stability problems due to erosion and land subsidence. In overcoming this problem, strengthening gabions is one solution that may be effective. For this reason, it is necessary to analyze slope stability accurately and effectively using software calculations and manual calculations. The software used for the analysis is Slope/W Analysis 2018. The research was carried out by testing low, medium and high tide water levels. The test results with these 12 conditions show the safety of natural slopes given earthquake loads at low water conditions. Safety Factor = 1.511; Medium water conditions Safety Factor = 1.617; High tide conditions Safety Factor = 1.746; Reinforced slopes are subjected to earthquake loads at low water conditions. Safety Factor = 1.910; Medium water conditions Safety Factor = 2.169; High tide conditions Safety Factor = 2.589; Natural slopes are subjected to earthquake loads and evenloads with low tide conditions. Safety Factor= 1.369; Medium water conditions Safety Factor = 1.455; High tide conditions Safety Factor = 1.690; Slopes with reinforcement and even load are given earthquake loads under low water conditions. Safety Factor = 1.653; Medium water conditions Safety Factor = 1.844; High tide conditions Safety Factor = 2.138